IMPLEMENTATION OF COMPETENCE APPROACH IN PROFESSIONAL TRAINING OF FOREIGN LANGUAGE TEACHERS-IN-TRAINING - Kharchenko , Tetiana; Udovichenko , Larysa; Zvereva , Maryna (Educological discourse, 2021)
The paper proves that applying reflexive practices in the training process at the specialized seminar on the analysis of practices is a significant component of the competence approach implementation. It was found out that training students to analyze complicated in-class situations under the supervision of an experienced trainer who observes, sets the paths, supports and assists them in interpreting their own methods of teaching and professional behavior, is an efficient technique of training. Studying the case of the module course called Analysis of Teacher’s Practices, introduced at the Higher National Institute of Education, Nice Academy, France (INSPE) proved that the active participation in the practices analysis seminar helps teachers-to-be develop new specific skills and competences based on their own experience. The paper highlights the principles of the organization of the seminars of practice analysis: the principles of ethics; of sincere interpretation; of contrast. It was stated that themes of seminars should be chosen in accordance with the students’ pedagogical probations. The authors formulate the targets of the seminars on the analysis of practices: making the knowledge of the subjects (including foreign languages) they teach more profound; further integration of interdisciplinary knowledge; mastering and developing narrow and specific knowledge in the subject they teach, as well as transversal knowledge of how help children study efficiently; developing reflexive state of a competent teacher. The paper proved that all the methods of the analysis of practices are based on different activities of the teacher-to-be themselves: memories and comparison of different lesson parts of whole lessons; the analysis of the teaching practices with the help of the supervisor; the analysis of “strengths” of the teaching practice; comparison of practical targets and results; the analysis of video recordings of lessons; the analysis of experienced teachers’ work; modelling and simulation of in-class situations. The perspectives of further research are a detailed study of the content of the course modules and phases of carrying out seminars.